Enclosing Ethnic Minorities and Forests in the Golden Economic Quadrangle - Janet C. Sturgeon (2018)
Ethnic minority farmers in the infamous Golden Triangle were first incorporated into the nation states of China, Laos and Thailand, and later into the economic region called the Golden Economic Quadrangle. This article traces policies in each country for minorities, development and the environment, followed by an analysis of agrarian transitions under economic regionalization. Using the framework of powers of exclusion and racialization, our findings show the changes for ethnic minorities who, with the exception of those in the lowlands, face environmental enclosures that dispossess them from lands on which livelihoods are based. Ideological legacies from the Golden Triangle, including 'backward' minorities, the fight against drugs, and threats to national security, continue to inform policies and development projects. While some farmers have become entrepreneurs planting cash crops, most face increasing marginalization under deepening regional capitalism. © 2013 International Institute of Social Studies.